Analysis of axial loaded pile in multilayered soil using nodal exact finite element model - Chinnapat Buachart (2018)
© 2018, Int. J. of GEOMATE. The nodal exact displacement based finite element method for analyzing axially loaded pile embedded in multilayered of finite depth of elastic soil is presented. The condition of shape function by which exact value may be reproduced at the nodal points regarding a few number of elements is investigated. The examined shape functions which satisfy the homogeneous governing equations in each layer of elastic soil are introduced to obtain the so-called exact element stiffness matrix. Then the stiffness matrix of proposed shape function was constructed via total potential energy principle. The results obtained from proposed finite element were compared with analytical solutions from literature. Axial force and displacement solutions of the pile embedded in multilayered soil obtained from proposed finite element model show exact agreement with analytical solutions and data from the available literature.